STRATEGI PUBLIC RELATIONS DALAM MEMBENTUK BRAND LOYALTY HOTEL SWISS-BELINN SKAPEKANBARU - Titi Ubudyah; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The hotel which winning for the category of three star hotel for the first ranked in Pekanbaru Tourism Award Night 2015 is Swiss-Belinn SKA Pekanbaru Hotel which always trying to provide good service for the guest through the public relations strategy that has been applied. Therefore, this study aim to determine and describe the public relations strategy for establish brand loyalty of Swiss-Belinn SKA Pekanbaru Hotel.This study uses descriptive qualitative research and supported by theories about the public relations strategy proposed by Harwood Childs. Subjects in this study are determined by purposive sampling technique which consists of Marketing and Communication Manager, Human Resource Staff, Executive Assistant Manager Room In Charge, and 4 guests of the hotel. Data collection techniques include interviews, observation and documentation. Techniques of analysis using models Miles and Huberman, interactive data with data validity checking used the technique extension of participation, persistence observation and triangulation.The results showed that Swiss-Belinn SKA Pekanbaru Hotel implement public relations strategies proposed by Harwood Childs which are publicity, persuasion, argumentation, and image. This strategy is implemented through the utilization of media, print media and online media as key factors in the process of implementing public relations strategy. In addition Swiss-Belinn SKA Pekanbaru also apply the important of awareness for living comfort in terms of services and facilities in order to get a good image in front of the guest. Meanwhile, the brand loyalty level of Swiss-Belinn SKA Pekanbaru Hotel are in the satisfied buyer. This is because the duration of the check-in make guests disappointed.Key word: Public relations, Strategy, Brand loyalty